PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBANTUAN APLIKASI CANVA TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD INPRES 5/81 LEMOAPE KABUPATEN BONE - arman, arman; Sudirman; Kadir, Abd (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is a quantitative research type of pre-experimental research with a pre-experimental research desaign in the form of a one-group pretest-posttest desaign which aims to determinate whether or not there is a significant effect of using the Canva-assisted Project Based Learning on the learning outcomes of IPAS class IV students of SD Inpres 5/81 Lemoape. This variables in this study are the Canva-assisted PjBL (independent variable) and IPAS learning outcomes (dependent variable). The population in this study were all students of SD Inpres 5/81 Lemoape as many as 190 students with a sampel as many as 20 students selected based on a cluster random sampling. The data collection technique used was a test to determine students IPAS learning outcomes before and after using the Canva-assisted PjBL. Based on the result of descriptive statistical analysis, the pretest average was 49,25 and the posttest average was 75,25. Meanwhile, based on the results of the normality test analysis, it shows that the posttest date are normally distributed, and the homogeneity test results show that the pretest and posttest date are homogeneous. The result of the hypothesis test show that there is a significant difference in students IPAS learning outcomes before and after using the Canva-assisted PjBL learning model. So it can be concluded that the Canva-assisted PjBL learning model influences the IPAS learning outcomes of students in class IV of SD Inpres 5/81 Lemoape.